Musical Tradition and Cultural Vision in Langston Hughes’s Poetry - Dhakal, Lekha Nath (Literary Studies, 2020)
In American music, Langston Hughes is one of the literary figures that hold a place similar to the aforementioned luminaries. In the literary field, Hughes is respected as one of the most important figures of the twentieth century. With the rise of African American Studies as an academic field in the 1970s, his life, writing, and influence has received frequent attention. What has not been documented in more specific terms is his importance to America’s musical culture in the twentieth century. Whether directly or indirectly, Langston Hughes has been a fixture in American musical culture, both popular and concert music, since the 1920s. In addition to his personal affinity for blues, jazz and other specifically African American musical forms such as gospel music, his vast contribution to American music specifically and American music culture in a broader sense can be separated into four general categories.